Quality and safety of meat from wild boar hunted in Molise region. Issue 1 (1st January 2021) - Palazzo, Marisa; Tavaniello, Siria; Petrecca, Valeria; Zejnelhoxha, Sanije; Wu, Mengjun; Mucci, Rossella; Maiorano, Giuseppe
Abstract: A study was carried out to evaluate meat quality traits and heavy metals content of longissimus thoracis muscle from wild boar of different estimated live weight (50, 70, 100 kg; n = 25, 24, 18, respectively), sex and hunting area of Molise region. Meat quality data were analysed by GLM, live weight and sex were the main factors, for heavy metals the hunting area was also included. Neither live weight nor sex affected pH, colour, vitamin E and total lipid. Cholesterol was tendentially affected by live weight and sex. Collagen content was affected only by sex. Lighter boars showed a higher content ( p <.05) of polyunsaturated fatty acid (PUFA), n − 6 and n − 3 PUFA, and PUFA/SFA ratio ( p <.05) compared to other weight classes. Lighter boars had a better atherogenic index compared to boars of intermediate weight. Compared to females, males (M) had higher n − 3 PUFA and a lower n − 6/n − 3 ratio ( p <.05). Weight, sex and hunting area did not affect cadmium (0.001 mg/kg), lead (0.011–0.026 mg/kg), copper (0.696–1.151 mg/kg) and manganese (0.083–0.130 mg/kg) levels. Chromium was affected by sex (M: 0.072 mg/kg; p =.012). Nickel (Ni) was higher ( p <.01) in the heaviest boars (0.035 mg/kg) than the other weight classes (0.017 mg/kg). Significant differences between the two areas were found for Ni content, interactions ( p <.01) were detected among all factors. In conclusion, lighter boars showed a better meat nutritional quality. The low content of heavy metals in the meat indicates a low level of anthropogenic pollution of the areas under study. Highlights: Meat from younger boars showed a better meat nutritional quality. Low levels of heavy metals in meat indicates a low level of anthropogenic pollution of the studied areas.